Māori Men's Experiences of Rehabilitation in the Moana House Therapeutic Community in Aotearoa/New Zealand: A Qualitative Enquiry - Ashdown, Jacob D. (International journal of offender therapy and comparative criminology, 2019)
In Aotearoa/New Zealand, culturally embedded rehabilitation programmes have been developed to reduce criminal offending among the indigenous Māori population. Currently, there is a lack of research investigating the experiences of these programmes from clients' perspectives. This study aimed to enhance understandings of the lived experiences of Māori men who were participating in a residential therapeutic community (TC) programme in Aotearoa/New Zealand. Semistructured interviews were conducted one-on-one by a psychology master's student who was a staff member at the TC and also of Māori descent. Seven Māori TC residents aged 22 to 48 were interviewed about life in a TC. Thematic analysis of the interview data yielded three themes: (a) "The importance of healing family relationships"; (b) "The relevance of Māori culture in rehabilitation"; (c) "Increased self-awareness." The findings highlight the significance of holistic approaches that emphasize culturally relevant approaches and the involvement of family members in the treatment of substance-use disorders and offending behaviour among indigenous populations.